Leaf epidermal morphology and petiole anatomy of the genus Anthocleista Afzel. ex R.Br. (Gentianaceae) - Jimoh, Muhali Olaide; Olowokudejo, James Dele (Journal of Tropical Agriculture, 2018)
Morphology of leaf epidermis and petiole transverse section in three species of Anthocleista was studied using a light microscope with a view to understanding the systematic significance of epidermal morphology and petiole anatomy within the genus. Interestingly, important taxonomic characters such as epistomata were observed in A. vogelii and amphistomata in A. djalonensis and A. nobilis. Scale trichomes were found in both epidermal layers of A. djalonensis and glandular trichome, which is multicellular and unicellular in A. nobilis and A. djalonensis respectively. Stomatal Index was highest at adaxial side of A. nobilis (10.14%), lowest at A. djalonensis (4.56%) and did not exist at all at the abaxial surface of A. vogelii. Common generic characteristics are polygonal cell shape, straight anticlinal wall, dendritic trichomes and petiole anatomy. The petiole is longest in A. nobilis, shortest in A. djalonensis and absent in A. vogelii. This work therefore, revealed that species within the genus differ in epidermal characteristics which could be used to delimit them although they share some similarities in cell geometry, petiole transverse section and anticlinal walls; all these are important taxonomic tools used in delimiting species in the genus.